LANGUAGE STYLE OF JOKOWI’S POLITICAL SPEECH - Syahputri, Diani (TELL - US JOURNAL, 2024)
The research deals with Language Style Jokowi’s Political Speech in event HUT TNI 72 Indonesian Declaration of Independence. The Objectives of The Study are several :1.) to describe the types of language style in Jokowi’s political speech in event HUT TNI ke-72 Indonesian Declaration of Independence.2.) to describe the ways of language style used by Jokowi in his political speech. The researches design is qualitative approach. technique for collecting data by using descriptive analysis technique. They describe the styles of language styles, and the dominantly of language styles The data are taken by https//m.detik.com/news/berita/ini-pidato-lengkap-jokowi-pimpin-Hut Dirgahyu- TNI- ke-72//. The data are transcribed into script and collected through the following steps which the researchers appley   by using   the script and observing the video of Jokowi’s political speech. The result, shows that there are nine Rhetorical meaning they are: Alliteration, Assonance, Anastrophe, Asyndeton, Pleonasm, Tautology, Paraphrasing  Prolepsis, Hyperbole and there are six figurative styles: Simile, Metaphor Personification, Metonymy, Synecdoche, Satire. The Rhetorical styles keep maintaining the real meaning, and mostly the use of the style does not give particular changing to the meaning of words uttered by Jokowi in his speech. However, the use of Rhetorical and Figurative style shows the non-literal meaning, since the meaning of the words form new meanings.